2019
DOI: 10.1093/nar/gkz856
|View full text |Cite
|
Sign up to set email alerts
|

Structure of tRNA methyltransferase complex of Trm7 and Trm734 reveals a novel binding interface for tRNA recognition

Abstract: The complex between Trm7 and Trm734 (Trm7–Trm734) from Saccharomyces cerevisiae catalyzes 2′-O-methylation at position 34 in tRNA. We report biochemical and structural studies of the Trm7–Trm734 complex. Purified recombinant Trm7–Trm734 preferentially methylates tRNAPhe transcript variants possessing two of three factors (Cm32, m1G37 and pyrimidine34). Therefore, tRNAPhe, tRNATrp and tRNALeu are specifically methylated by Trm7–Trm734. We have solved the crystal structures of the apo and S-adenosyl-L-methionine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 69 publications
2
35
0
Order By: Relevance
“…During the submission of our work, the biochemical and structural studies of S. cerevisiae Trm7-Trm734 (PDB ID: 6JP6) have been published online (Hirata et al, 2019). The structural model shows that Trm7 is a class I-type Rossmann-fold MTase, and Trm734 comprises three WD40 repeat domains (Hirata et al, 2019).…”
Section: Wdr6 At Position 34 (mentioning
confidence: 99%
See 3 more Smart Citations
“…During the submission of our work, the biochemical and structural studies of S. cerevisiae Trm7-Trm734 (PDB ID: 6JP6) have been published online (Hirata et al, 2019). The structural model shows that Trm7 is a class I-type Rossmann-fold MTase, and Trm734 comprises three WD40 repeat domains (Hirata et al, 2019).…”
Section: Wdr6 At Position 34 (mentioning
confidence: 99%
“…During the submission of our work, the biochemical and structural studies of S. cerevisiae Trm7-Trm734 (PDB ID: 6JP6) have been published online (Hirata et al, 2019). The structural model shows that Trm7 is a class I-type Rossmann-fold MTase, and Trm734 comprises three WD40 repeat domains (Hirata et al, 2019). They showed that Trm7-Trm734 are able to catalyze both G37-and A37-tRNAs for Nm34 formation and that m 1 G37 is not an essential element for catalysis (Hirata et al, 2019).…”
Section: Wdr6 At Position 34 (mentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 5 B illustrates a validation in solution of the heterodimeric complex between the tRNA methyltransferase Trm7 and its partner subunit Trm734 from Saccharomyces cerevisiae ( Hirata et al. 2019 ).…”
mentioning
confidence: 99%